Student Perceptions of Online Examinations as an Emergency Measure during Covid-19 - Piera Biccard; Patience Kelebogile Mudau; Geesje van den Berg (Journal of Learning for Development, 2023)
This article explores student perceptions of writing online examinations for the first time during the Covid-19 pandemic. Prior to the pandemic, examinations at an open and distance learning institution in South Africa were conducted as venue-based examinations. From March 2020, all examinations were moved online. Online examinations were introduced as an emergency measure to adhere to safety and health protocols. Although students in developed countries have indicated benefits to online examinations, less is known about students living in the Global South when it comes to writing examinations online. Not enough is known about the benefits and challenges of online examinations since they were implemented as an emergency measure. We aimed at  exploring student perceptions of writing online examinations for the first time, improve examination processes by including student views. Through an analysis of 336 written responses to an open-ended question posed at the end of an online survey, we established that digital access, duration of the examination, and the examination system interface affected students’ success in online examinations. Based on the findings, we recommend that students need to be given tools and data to participate in online examinations. Furthermore, students should be granted ample opportunity to practise writing online examinations while receiving the necessary support.